2017
DOI: 10.1002/pola.28695
|View full text |Cite
|
Sign up to set email alerts
|

Ring opening metathesis polymerization (ROMP) of five‐ to eight‐membered cyclic olefins: Computational, thermodynamic, and experimental approach

Abstract: Ring opening metathesis polymerization (ROMP) of a series of low-strain cyclic olefins and their hydroxyl derivatives using second generation Hoveyda-Grubbs catalyst has been investigated. Additionally, density functional theory (DFT) calculations were performed to evaluate the ring strain energies of the cyclic olefins and their hydroxyl derivatives, coupled with kinetic studies for the ROMP reactions. It was found that among different ring size monomers, Cy8 having a relatively moderate ring strain energy in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(96 citation statements)
references
References 43 publications
4
88
0
Order By: Relevance
“…30%). We had thought that this may be due to lower ring strain, but calculations (similar to recent results) showed that monomer 13 had a ring strain energy of 13.8 kcal/mol while monosubstituted 6 has 11.8 kcal/mol (Table S3, Supporting Information). Interestingly though, 13 could be successfully polymerized under more typical ROMP conditions (strict oxygen‐free conditions in CH 2 Cl 2 with [ 13 ] = 0.6 M) and higher initiator loading ([ 13 ]:[ 7 ] = 50:1) to provide polymer 14 as a gummy solid by precipitation into methanol in 75% yield.…”
Section: Resultssupporting
confidence: 67%
“…30%). We had thought that this may be due to lower ring strain, but calculations (similar to recent results) showed that monomer 13 had a ring strain energy of 13.8 kcal/mol while monosubstituted 6 has 11.8 kcal/mol (Table S3, Supporting Information). Interestingly though, 13 could be successfully polymerized under more typical ROMP conditions (strict oxygen‐free conditions in CH 2 Cl 2 with [ 13 ] = 0.6 M) and higher initiator loading ([ 13 ]:[ 7 ] = 50:1) to provide polymer 14 as a gummy solid by precipitation into methanol in 75% yield.…”
Section: Resultssupporting
confidence: 67%
“…For large, strainless macrocycles the influence of olefin stereochemistry does not originate from differential ring strain. Instead, a slight enthalpic benefit is associated with ring‐opening of cis ‐olefinic macrocycles due to alleviation of steric repulsion between nearby bulky groups on the same side of the double bond . As the monomers are ring‐opened and cycloreversion of the metallocyclobutane occurs, new olefins are produced in the polymer backbone with stereochemistry defined by the approach of the monomer relative to the catalyst‐bound alkylidene.…”
Section: Considerations Of Ed‐rompmentioning
confidence: 99%
“…The ranking methodology proposed herein first normalized all the data set to make distinction between the DEA efficient units. The data set (both input and output) normalization was done with the help of Equation (5). By doing this the "maximin" weight of each DEA efficient unit was protected from any effect of scaling transformations of inputs and output.…”
Section: Results Of Dea and Different "Minimum Weight Restriction"mentioning
confidence: 99%